The impact of working capital management on manufacturing firms' profitability - an emerging market perspective - Arulanandam, Benedict Valentine*; Glinkowska-Krauze, Beata; Tan, Pei Yu (Silesian University of Technology Publishing House, 2023)
Purpose: This study aims to investigate the effects of working capital management on firm profitability of listed manufacturing companies in Malaysia. Design/methodology/approach: This study uses account payables, inventory turnover, account receivables, cash conversion cycle, firm size, growth, leverage and current ratio as accounting information variables. Secondary data was collected for all variables over a ten-year period, i.e. 2009 to 2018 and was obtained from the annual report published via Bursa Malaysia (Malaysian Stock Exchange) official website. Data was analyzed by using IBM SPSS Statistics Subscription software. Descriptive statistics, correlation analysis and multiple regression analysis were utilized in this study. Findings: The results revealed that inventory turnover in days, account receivables and firm size have a positive significant relationship with manufacturing firms’ profitability, while account payables and cash conversion cycle have a positive insignificant relationship. Research limitations/implications: The sample size is too small for any generalization. A mixed method approach in the future could contribute to a holistic finding. Practical implications: Since these variables contained significant influence on firm profitability, it is recommended that listed manufacturing companies should prepare a complete and timely manner of accounting information based on the regulation context in Malaysia. Social implications: It provides an empirical evidence on the importance of working capital management amongst the manufacturing concerns in Malaysia and its impact on its business sustainability. Originality/value: This study contributes to the limited research on working capital management involving manufacturing companies in Malaysia.